Grammatical Polymorphism Between Consideration and Inference (Islamic Sciences Journal, 2023)
ABSTRACT                        The grammar of the Arabic Language has received the attention of its scholars .They were interested in reclining the grammatical rule and install the pillars of these bases which made them take care of the order of its sentences until they became    readymade templates among the scholars .It is covered in a later lesson from an earlier one . It was among their cocern with those rules, their attention to multiple ranks in one sentence to give this multiplicity an addition benefit that didant exist in the sentence without plurality. This multiplicity was the intention of the Arabic speaker to lead to use on the one hand and a mural benefit deroid of the Arabic sentence if there is no multiplicity in it.